A case study on the welfare of tigers in captivity of National zoo and Malacca zoo (looking at the law) / Azleen Melorina Adnan, Noor Nafni Munjir and Nourmayusniza Talif - Adnan, Azleen Melorina; Munjir, Noor Nafni; Talif, Nourmayusniza (Faculty of Law, 2007)
The objective of this legal research project is to come out with a new set of rules and regulations which govern the zoos in handling endangered species such as Malayan Tigers. There is no standard procedure established as yet. The fact that where tigers in zoos are concerned, there is absence of law in regulating zoo's activities in handling this wildlife. Therefore, this work will focus on the weaknesses of the current methods in handling the species. The scope of this legal research is on the tiger's welfare in Malaysia's zoo and as the reference, we studied on how the two main zoos in Malaysia namely, National Zoo and Malacca Zoo maintain the species. This research will be based on the books, articles, magazines, journals and other suitable materials from the law library of Universiti Teknologi MARA (PTAR UiTM) and also Universiti Malaya's (UM) main library. Besides, an interview with the National Zoo's Zoological Head of Department is conducted to gather the information regarding this issue. Questionnaires were also distributed to several respondents in order to gain views and opinions in assisting us upon completion of this research. It is hoped that this legal research will provide a comprehensive discussion on the loopholes pertaining the issue of how the Malaysian Zoo's authority handle the welfare of the wildlife, specifically tigers. There is a need of law to control their power to overcome the problems and difficulties as they are not bound to follow any rules and regulations.